Negara Dalam Keadaan Darurat Menurut UUD 1945 - Mirza Sahputra (Puslatbang KHAN, 2020)
In the 1945 Constitution of the Republic of Indonesia (1945 Constitution), the provisions concerning emergencies (state of emergency) are regulated in two articles, namely Article 12 which states